Pembiayaan Mikro BRI Syariah: Upaya Pemberdayaan dan Peningkatan UMKM oleh BRI Syariah Cabang Kendari - Turmudi, Muhamad (Li Falah: Journal of Islamic Economics and Business, 2017)
Understanding of micro, small and medium enterprises is based on indicators (1) the amount ofwealth such as cash, supplies, land, machinery for production (2) the amount of investment that isconsidered as working capital (3) total sales in a year (4) total number of employees.Micro Business Financing BRI Syariah is a business financing product intended for middle classpeople who have micro, small and medium enterprises to meet the needs/capital increase. in an effortto increase Micro, Small and Medium Enterprises in Kendari City, BRI Syariah has three financingproducts for Micro, Small and Medium Enterprises; (1) Micro 25iB; is a product without collateralfinancing, the ceiling of Rp. 5juta to Rp. 25juta (2) Micro 75iB; is a financing product with collateral,the ceiling of Rp. 10juta to Rp. 75M (3) Micro 500iB; is a financing product with collateral, theceiling of Rp. > 75juta to Rp. 500million.